Penggantian Kateter Intravena Perifer sesuai Indikasi Klinis terhadap Kejadian Komplikasi pada Anak - Khusnul Khotimah; Nani Nurhaeni; Imami Nur Rachmawati (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of peripheral intravenous catheter replacement on clinical indications of complications in children. The method used is a review of eight articles on the impact of intravenous catheter replacement on clinical presentations on the incidence of complications in children using the ScienceDirect, ProQuest, Ebscohost, and Scopus databases. The inclusion criteria for the articles reviewed were research articles published in 2002-2022, accessible in full text and English. The exclusion criteria were articles not accessible in full text and check reports. The study's results obtained eight pieces that followed the study's objectives. The results of a systematic review of complications, 4 of 8 research articles showed that intravenous catheter replacement according to clinical indications did not significantly increase the risk of intravenous catheter complications; three research articles showed no significant difference to intravenous catheter complications.Regarding the survival time of intravenous catheters, of the eight articles reviewed, three reports stated that those replaced based on clinical indications had a longer survival time than those replaced routinely. Meanwhile, from cost efficiency, three articles said that routine catheter replacement increased hospital expenses. In conclusion, replacing intravenous catheters according to clinical indications has a more positive effect on pediatric patients. If surveillance for signs and symptoms of intravenous catheter complications is carried out regularly, signs of intravenous catheter complications can be detected early. Keywords: Extravasation, Phlebitis, Infection, Infiltration, Peripheral Intravenous Catheter, Intravenous Catheter Replacement